Revisiting Early Jurassic Biscutaceae: Similiscutum giganteum sp. nov. - Mailliot, Samuel (2023)
A large, broadly elliptical coccolith of the genus Similiscutum (Biscutaceae) was observed in sediments dated from the Lower Jurassic (upper Pliensbachian to Toarcian) coming from different localities of western Tethys, namely Portugal (Lusitanian Basin), France (Causses and Paris basins) and Spain (Subbetic area). This form is quite easy to find in the Toarcian GSSP (Global Stratotype Section and Point) of Peniche (Portugal), where the holotype has been described. More than 100 specimens of Similiscutum were digitally captured using a CCD camera, including this large form and two other related species, Similiscutum finchii and Similiscutum novum. The length and width of the coccoliths and the length and width of their central area were measured, and biometric analyses were performed. Results show that this large morphotype of Similiscutum is well characterized and easily differentiable by its size and morphology from the species S. finchii and S. novum, which are characterized by a similar extinction pattern in optical-microscope crossed polars . On the basis of combined differences in size and in central-area shape and structure, Similiscutum giganteum sp. nov. is introduced here. (Plant Fossil Names Registry no.: PFN003067; Act LSID: urn:lsid:plantfossilnames.org:act:3067).